PENGARUH VARIASI PARAMETER PENGELASAN (PUTARAN DAN TEMPERATUR) TERHADAP KEKUATAN SAMBUNGAN LAS HASIL FRICTION WELDING PADA BAJA KARBON RENDAH - Iswar, Muhammad; Syam, Rafiuddin (Jurnal MEKANIKAL, 2012)
This study aims to analyze the influence of rotation and temperature on the strength of welded joints (tensile strength and strain stress) from the result of friction welding using low carbon steel (St.42). The Friction welding process was carried out by varying the rotation (550 rpm, 1020 rpm and 1800 rpm) and temperature (750oC, 800oC and 850oC). The results of the friction welding were then examined to find out their connections strength. The initial data of this research were obtained through the testing of tensile stress and strain stress by using the tensile testing machine and the torsion testing machine. The data obtained from the tests were analyzed by using statistical methods of regression and ANOVA. The results reveal that the maximum tensile strength value ​​and the highest maximum strain stress occur at the rotation of 1800 rpm  and the temperature of 850oC. The values were: σmax = 403.80 N/mm2 and ד max = 365.89 N/mm2. The statistical analysis reveals that there is a relationship betwen the input variable X (rotation and temperature) and output  variable Y (tensile strength and strain stress)